Fibrillin-1 genetic deficiency leads to pathological aging of arteries in mice - Mariko, B (2011)
Fibrillin-1, the major component of extracellular microfibrils that associate with insoluble elastin in elastic fibers, is mainly synthesized during development and postnatal growth and is believed to guide elastogenesis. Mutations in the fibrillin-1 gene cause Marfan syndrome, a multisystem disorder characterized by aortic aneurysms and dissections. The recent finding that early deficiency of elastin modifies vascular aging has raised the possibility that fibrillin-1 deficiency could also contribute to late-onset pathology of vascular remodeling. To address this question, we examined cardiovascular function in 3 week-old, 6 month-old, and 24 month-old mice that are heterozygous for a hypomorphic structural mutation of fibrillin-1 (Fbn1(+/mgΔ) mice). Our results indicate that Fbn1(+/mgΔ) mice, particularly those that are 24 month-old, are slightly more hypotensive than wild-type littermates. Additionally, aneurysm and aortic insufficiency were more frequently observed in aging Fbn1(+/mgΔ) mice than in the wild-type counterparts. We also noted substantial fragmentation and decreased number of elastic lamellae in the aortic wall of Fbn1(+/mgΔ) mice, which were correlated with an increase in aortic stiffness, a decrease in vasoreactivity, altered expressions of elastic fiber-related genes, including fibrillin-1 and elastin, and a decrease in the relative ratio between tissue elastin and collagen. Collectively, our findings suggest that the heterozygous mgΔ mutation accelerates some aspects of vascular aging and eventually lead to aortic manifestations resembling those of Marfan syndrome. Importantly, our data also indicate that vascular abnormalities in Fbn1(+/mgΔ) mice are opposite to those induced by elastin haploinsufficiency during aging that affect blood pressure, vascular dimensions and number of elastic lamellae.